Ò7 Evaluation of antibacterial and antiviral activity of N-arylamides of 9-methyl- and 9-methoxyphenazine-1-carboxylic acids – inhibitors of the phage T7 model transctiption - Palchykovska, L.G.; Vasylchenko, O.V.; Platonov, M.O.; Kostina, V.G.; Babkina, M.M.; Tarasov, O.A.; Starosyla, D.B.; Samijlenko, S.P.; Rybalko, S.L.; Deriabin, O.M.; Hovorun, D.M. (Вiopolymers and Cell, 2012)
Aim. Search for compounds with antibacterial and antiviral properties among N-arylamides of 9-substituted phenazine-1-carboxylic acids (PCA), inhibitors of the RNA synthesis. Methods. Influence of N-aryl-amides on the RNA synthesis was tested in vitro in the model system of the DNA-dependent RNA polymerase of phage T7 (T7 RNAP). Antimicrobial activities of the N-arylamides against bacteria Erysipelothrix rhusiopathiae VR-2 var. IVM, Klebsiella spp. and Escherichia coli ATCC25922 were investigated by the method of two-fold dilution in a liquid medium. Antiviral effects against Bovine Viral Diarrhea Virus (BVDV) and cytotoxicity of the N-arylamides were evaluated using Madin-Darby bovine kidney (MDBK) cells. Results. Twenty N-arylamides appeared to be efficacious inhibitors of the RNA synthesis at concentrations of 0.48–61 µM. The compound 16 proved to be the most effective inhibitor of T7 RNAP with the IC50 value being 0.48 µM. Fourteen N-arylamides demonstrated antibacterial properties against gram positive and gram negative bacteria at the 0.1–10 µg/ml concentrations. A number of the N-arylamides revealed a multiplicity of their antimicrobial actions: 7 compounds against two bacteria and two compounds, 2 and 3, against three bacteria investigated. N-arylamides 16 and 26 showed high inhibitory activity as to BVDV with the IC50 values 0.43 and 0.88 µg/ml and SI values 160 and 10 correspondingly. Conclusions. The obtained data evidence that the most likely targets of the N-arylamides 9-substituted PCA in bacteria and viruses are their RNA synthesizing complexes.
Keywords: N-arylamides 9-substituted PCA, model system of the DNA-dependent RNA-polymerase of phage T7, antibacterial activity, antiviral activity. Мета. Пошук серед N-ариламідів 9-заміщених феназин-1-карбонових кислот (ФКК-1) – інгібіторів синтезу РНК – сполук з антибактерійними та антивірусними властивостями. Методи. Вплив N-ариламідів на синтез РНК in vitro визначали із застосуванням модельної системи ДНК-залежної РНК-полімерази бактеріофага Т7; антимікробну активність N-ариламідів – методом дворазових розведень у рідкому середовищі проти бактерій Erysipelothrix rhusiopathiae VR-2 var. IVM, Klebsiella spp. та Escherichia coli ATCC25922. Антивірусну дію щодо вірусу бичачої вірусної діареї (ВБВД) і цитотоксичність N-арил-амідів оцінювали на перещеплюваній лінії культури клітин нирки теляти. Результати. Двадцять N-ариламідів виявилися ефективними інгібіторами синтезу РНК у межах концентрацій 0,48–63 мкМ. Найвищу активність продемонструвала сполука 16, ІС50 якої становить 0,48 мкМ. Антибактерійні властивості стосовно грампозитивних і грамнегативних бактерій проявили 14 N-ариламідів при концентраціях 0,1– 10 мкг/мл. Для низки N-ариламідів встановлено множинний характер антибактерійної дії: сім сполук проти двох і дві (2 і 3) – проти трьох досліджуваних бактерій. N-ариламіди 16 і 26 виявили високу інгібіторну здатність проти ВБВД з показниками ІС50 0,43 і 0,88 мкМ і SІ > 160 і 10 відповідно. Висновки. Отримані результати дають підставу вважати, що вірогідними мішенями для N-ариламідів 9-заміщених ФКК-1 у бактерій і вірусіможуть бути є їхні РНК-синтезувальні комплекси.
Ключові слова: N-ариламіди 9-заміщених ФКК-1, модельна система транскрипції фага Т7, антибактерійна активність, антивірусна активність. Цель. Поиск среди 9-замещенных N-ариламидов феназин-1-карбоновой кислоты (ФКК-1) – ингибиторов синтеза РНК – соединений с антибактериальными и антивирусными свойствами. Методы. Влияние N-ариламидов на синтез РНК in vitro определяли с использованием модельной системы ДНК-зависимой РНК-полимеразы бактериофага Т7; антимикробную активность N-арил- амидов – методом двукратных розведений в жидкой среде против бактерий Erysipelothrix rhusiopathiae VR-2 var. IVM, Klebsiella spp. и Escherichia coli ATCC25922. Антивирусное действие по отношению к вирусу бычьей вирусной диареи (ВБВД) и цитотоксичность N-ариламидов оценивали на перевиваемой линии культуры клеток почки теленка. Результаты. Двадцать N-ариламидов оказались эффективными ингибиторами синтеза РНК в диапазоне концентраций 0,48–63 мкМ. Наивысшую активность продемонстрировало соединение 16, ІС50 которого составляет 0,48 мкМ. Антибактериальные свойства относительно грампозитивных и грамнегативных бактерий проявили 14 N-ариламидов в концентрациях 0,1–10 мкг/мл. Для ряда N-ариламидов установлен множественный характер антибактериального действия: семь соединений против двух, а два (2 и 3) – против трех исследуемых бактерий. N-ариламиды 16 и 26 выявили высокий ингибиторный потенциал против ВБВД с показателями ІС50 0,43 и 0,88 мкМ и SІ > 160 и 10 соответственно. Выводы. Полученные результаты дают основание полагать, что возможными мишенями для N-арил-амидов 9-замещенных ФКК-1 у бактерий и вирусов могут быть их РНК-синтезирующие комплексы.
Ключевые слова: N-ариламиды 9-замещенных ФКК-1, модельная система транскрипции фага Т7, антибактериальная активность, антивирусная активность.